Strategi Ustadzah Untuk Meningkatkan Motivasi Lansia Dalam Pembelajaran al-Qur’an - Aprilia Ayu Nila Sari; Faridi; Zulfikar Yusuf (Journal of Islamic Education Management, 2022)
This study aims to describe the efforts of muslim teacher in providing motivation to the elderly in the Ta'lim Nur Hasanah Sawojajar Malang Council. This research uses a qualitative approach with the type of case study research. While the objects in this study were the chairman of the assembly, ustadzah and 5 elderly people at the Ta'lim Council of Nur Hasanah Sawojajar Malang. The selection of the Ta'lim Council of Nur Hasanah Sawojajar Malang as a research site was based on the lack of people who no longer studied the Qur'an, but it turned out that there were still elderly people who had various limitations starting to study the Qur'an. With these limitations, the researcher wants to know the efforts of the cleric in motivating the elderly to continue to be istiqomah in studying the Qur'an. Data was collected through observation, interview, and documentation techniques. Meanwhile, data analysis was carried out by collecting data, reducing data, presenting data and making conclusions. The results showed that: the efforts given by the cleric were: 1). Awakening the interest of the elderly to return to reading the Qur'an, 2). Creating a pleasant learning atmosphere, and 3). Instilling positive values ​​in everyday life.